Langman's medical embryology - Sadler, T. W. (Philadelphia : Wolters Kluwer, 2019)
Every student will be affected by pregnancy, either their mother's, because what happens in the womb does not necessarily stay in the womb, or by someone else's. As health care professionals, you will often encounter women of childbearing age who may be pregnant, or you may have children of your own, or maybe it is a friend who is pregnant. In any case, pregnancy and childbirth are relevant to all of us, and unfortunately, these processes often culminate in negative outcomes. For example, 50% of all embryos are spontaneously aborted. Furthermore, prematurity and birth defects are the leading causes of infant mortality and major contributors to disabilities. Fortunately, new strategies can improve pregnancy outcomes, and health care professionals have a major role to play in implementing these initiatives. However, a basic knowledge of embryology is essential to the success of these strategies, and with this knowledge, every health care professional can play a role in providing healthier babies. To accomplish its goal of providing a basic understanding of embryology and its clinical relevance, Langman's Medical Embryology retains its unique approach of combining an economy of text with excellent diagrams and clinical images. It stresses the clinical importance of the subject by providing numerous clinical examples that result from abnormal embryological events. The following pedagogic features and updates in the 14th edition help facilitate student learning--Provided by publisher.
Includes bibliographical references and index.
Keywords: Congenital Abnormalities; Embryonic Development; Fetal Development